2013
DOI: 10.1016/j.jallcom.2013.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen absorption study of high-energy reactive ball milled Mg composites with palladium additives

Abstract: Hydrogenation behaviour, structure, morphology and dehydrogenation/rehydrogenation performances of Mg-Pd nanocomposites prepared by high-energy reactive ball milling in H2 (HRBM) of Mg in the presence of amorphous and crystalline Pd black (0.1-5 wt.%) were studied. Improvements of hydrogenation kinetics during HRBM were observed only for the materials prepared using crystalline Pd black. The obtained nanocomposites were characterised by modest improvements in their dehydrogenation and re-hydrogenation performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
1
3
0
1
Order By: Relevance
“…[46] reveals that the better hydrogenation behaviour possessed by milled alloys can be attributed to their combination of tetragonal (a = 4.52 Å, c = 3.02 Å) and orthorhombic (a = 4.48 Å, b = 5.40 Å, c = 4.90 Å) phases as major phases, since these two phases are associated with small particle size and a presence of strain in the particles. Similar trends of hydrogen capacity and kinetics were observed by Lototskyy et al [47] and Williams et al [48] when they assessed Mg-10(FeV)-5MWCNT and Mg-5Pd composites through mechanical alloying, respectively. Tables 2 and 3 represent a compiled data of literature based on hydrogenation behaviour of Mg-based alloy materials synthesized through ball milling and mechanical alloying.…”
Section: Hydrogen Absorption Behaviour Of Mechanically Alloyed Mg-bas...supporting
confidence: 81%
“…[46] reveals that the better hydrogenation behaviour possessed by milled alloys can be attributed to their combination of tetragonal (a = 4.52 Å, c = 3.02 Å) and orthorhombic (a = 4.48 Å, b = 5.40 Å, c = 4.90 Å) phases as major phases, since these two phases are associated with small particle size and a presence of strain in the particles. Similar trends of hydrogen capacity and kinetics were observed by Lototskyy et al [47] and Williams et al [48] when they assessed Mg-10(FeV)-5MWCNT and Mg-5Pd composites through mechanical alloying, respectively. Tables 2 and 3 represent a compiled data of literature based on hydrogenation behaviour of Mg-based alloy materials synthesized through ball milling and mechanical alloying.…”
Section: Hydrogen Absorption Behaviour Of Mechanically Alloyed Mg-bas...supporting
confidence: 81%
“…Generally, adding additives or catalysts is considered as one of the most effective strategy to decrease the metal-hydrogen bonds energy and reduce the desorption energies of MgH 2 [3][4][5][6][7]. Among all the additives, the unique electrical and chemical properties of Ti-based materials make them promising for MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Another efficient strategy consists in milling a catalyst with MgH 2 . Palladium93 or other transition metals,94 intermetallic compounds such as LaNi 5 95 and TiF 3 ,96 and metal oxides such as Nb 2 O 5 97 have been used. For example, it has been shown that the milled composite MgH 2 –FeTi uptakes approximately 5 wt % H 2 at 300 °C under 20 bar H 2 within 3000 s (Figure 4); the adsorption rate is fast, as 90 % of the maximum capacity of MgH 2 is reached within 1 min 98.…”
Section: Materials For Reversible Hydrogen Storagementioning
confidence: 99%